Self-assembled monolayer dielectrics for low-voltage carbon nanotube transistors with controlled network density - Schießl, Stefan Patrick; Gannott, Florentina; Etschel, Sebastian H.; Schweiger, Kai Manuel; Grünler, Saeideh; Halik, Marcus; Zaumseil, Jana (Advanced materials interfaces, 2016)
Control of the density and uniformity of semiconducting single-walled carbon nanotube (SWNT) networks is crucial for their application in field-effect transistors (FETs) and critically depends on the surface of the substrate. Here, the concept of self-assembled monolayer (SAM) dielectrics on aluminum/aluminum oxide bottom-gate electrodes is used to create low-voltage (<2 V) FETs with SWNT networks.